Atividade imunomoduladora da ouabaína no processo inflamatório agudo - Leite, Jacqueline Alves (2012)
Ouabain (OUA), a potent inhibitor of the Na+,K+-ATPase pump, was identified as an endogenous substance of human plasma. In recent years, ouabain was shown to affect various immunological processes. Mechanisms that involve cellular differentiation, proliferation, activation and migration, as well as inflammatory mediators release, are activated during inflammation and homeostasis is usually reestablished. This study demonstrated the modulatory ability of OUA on inflammatory process. Aim: This study aimed to evaluate ouabain immunomodulatory role on acute inflammatory process using a murine model. Methods: Initially, a dose and time-response curve was performed with OUA (0.10 mg/kg, 0.31 mg/kg and 0.56 mg/kg) intraperitoneally administered on the paw edema induced by zymosan (10 mg/mL). Mice were also intraperitoneally (i.p.) stimulated with zymosan (2 mg/mL). After 4h, the peritoneal fluid was removed for total and differential cell counts. Neutrophils and macrophages population, as well as cell viability, were analyzed using an annexin KIT by flow cytometry. The concentrations of the cytokines IL-1β, TNF-α, IL-6 and IL-10 in peritoneal lavage fluids were assayed using ELISA kit. Ouabain influence in the vascular permeability increase was determined using evans blue dye. OUA, in vitro, influence on nitric oxide (NO) production was also studied. Results: It was observed that OUA 0,56 mg/kg injected for three consecutive days prevented zymosan edema formation . After induction of inflammation, treatment with OUA led to a 42% reduction in the total cell numbers in the peritoneal cavity, as a reflex of the inhibition of polymorphonuclear leukocytes (54%), which was not due to cell apoptosis. Ouabain also decreased zymosan-induced plasma exudation (33%). Furthermore, OUA decreased the levels of TNF-α (64%) and IL-1β (63%), without interference on IL-6 and IL-10 levels. It was also demonstrated, using peritoneal macrophages, that ouabain did not interfere on LPS induced NO production. Conclusion: Ouabain modulated the acute inflammatory response induced by zymosan. However, further studies are necessary to elucidate the mechanisms involved